PENGARUH PEMBERIAN CORNMEAL DAN CORNMEAL-SOY TERHADAP KADAR KOLESTEROL DALAM SERUM TIKUS - Harti, Leny Budhi; Rudijanto, Achmad; Kristianto, Yohanes (Fakultas Kedokteran Universitas Brawijaya, 2008)
Coronary Heart Diseases (CHD) are a serious health problem that commonly occur not only in modern countries, but aslo in developing countries like Indonesia. The high cholesterol level in blood is a risk factor that may cause CHD by atherosclerosis mecanism. dietary fiber may be used to prevent atherosclerosis. Cornmeal and cornmeal-soy are products of corn, that rich in fiber. This research was aimed to study about the effect of cornmeal and cornmeal-soy on serum cholesterol level of 6-8 mounths male wistar rats. The subjects are 25 male wistar rats. These mice will be provided into five groups. (1) gruop that given atherogenic diet only, (2) gruop that given atherogenic diet with cornmeal 3.4 g/day, (3) gruop that given atherogenic diet with cornmeal 6.8 g/day, (4) gruop that given atherogenic diet with cornmeal-soy 3.6 g/day, (5) gruop that given atherogenic diet with cornmeal-soy 7.2 g/day. Data collecting include first weight, last weight, weight gain, nutrient intake, and serum lipid. Statistic analysis that be used is ANOVA one way. Results showed that wistar rats which given atherogenic diet with cornmeal and cornmeal-soy had trend to increase cholesterol and LDL level. According to statistic analysis, cholesterol and LDL level among groups were not significant (p > 0.05). However wistar rats which given atherogenic with cornmeal and cornmeal-soy in high doses,